2022
DOI: 10.3390/vaccines10050768
|View full text |Cite
|
Sign up to set email alerts
|

In-Person Schooling Amidst Children’s COVID-19 Vaccination: Exploring Parental Perceptions Just after Omicron Variant Announcement

Abstract: Background: The SARS-CoV-2 Omicron spread fast globally and became the predominant variant in many countries. Resumption of public regular life activities, including in-person schooling, presented parents with new sources of worry. Thus, it is important to study parental worry about the Omicron variant, willingness to vaccinate their children, and knowledge about school-based COVID-19 precautionary measures. Methods: A national, cross-sectional, pilot-validated online questionnaire targeting parents in the Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The acceptance of booster COVID-19 vaccination in the Eastern Mediterranean region was 59% (95% CI: 46–71%, I 2 = 99%), ranging from 71% (95% CI: 69–73%) [ 81 ] to 43% (95% CI: 40–46%) [ 62 ] ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The acceptance of booster COVID-19 vaccination in the Eastern Mediterranean region was 59% (95% CI: 46–71%, I 2 = 99%), ranging from 71% (95% CI: 69–73%) [ 81 ] to 43% (95% CI: 40–46%) [ 62 ] ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The emergence of the Monkeypox disease in May 2022 across the globe has caused significant worry among the public, especially with the still ongoing Coronavirus Disease 2019 (COVID-19) pandemic [ 1 ]. It has previously been demonstrated that the level of worry and concern about the evolving COVID-19 has been exemplified by the different variants, such as the Delta and Omicron [ 2 , 3 ]; therefore, the co-emergence of a new virus potentially might complicate the anxiety and worry levels across the different sectors of the public.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that theory-based behavioral interventions are more effective [ 4 - 9 ]. However, rather than building on the premise of theoretical models to test hypotheses, most studies [ 10 - 12 ] that have collected data to conduct exploratory studies of knowledge, attitudes, and beliefs or have focused on demographic factors related to vaccination practices.…”
Section: Introductionmentioning
confidence: 99%